Impacts of Social Forestry Programmes on Local Communities and Forest Conditions in West Kalimantan, Indonesia - Sudarna, Anang (2001)
The goal of the study was to evaluate social forestry programmes as an approach towards achieving the goal of sustainable forest management (SFM) by assessing the impacts and outcomes of these programmes on the socioeconomic condition of local communities and forest resource conditions. Surveys utilising structured closed-ended questionnaire were carried out on a random sample of 450 participants and 150 non-participants of the programmes of nine selected villages. Informal interview, direct observation, and small group discussion were also conducted to collect the required information. This research found different impacts at different locations. The programme has caused significant impacts on school going children and training opportunities at one location; on rice production, application of IAT, employment opportunities, training courses, and farmers' skills at another location. However,· at both locations the programme failed to improve forest conditions. However, programme implemented at the 3rd location has reduced shifting cultivation and people dependency on forest-based activities, but has increased planting HYV of rubber, employment opportunities, training, farmers' skills, and awareness on the importance of forest sustainability. The programme at this location has also shown promises at increasing forest resource conditions. Above all, the programmes at all locations failed to increase the income of forest-dependent communities. The different findings at different locations were due mainly to different approaches applied in the programme planning and implementation.